Randomised phase II trial of stereotactic body radiotherapy in combination with checkpoint inhibitors in metastatic castration-resistant prostate cancer (CheckPRO): a study protocol - Henriette Lindberg; Inge Marie Svane; Estrid V Hogdall; Dorte Lisbeth Nielsen; Susann Theile; Nicklas Juel Spindler; Gitte Fredberg Persson; Gina Al-Farra; Helle Westergren Hendel; Torben Lorentzen; Rikke Løvendahl Eefsen (BMJ Open, 2023)
Introduction Immunotherapy with checkpoint inhibitors (CPIs) has revolutionised cancer treatment but has no convincing effect in metastatic castration-resistant prostate cancer (mCRPC). It has been suggested that a combination of CPI and hypofractionated stereotactic body radiotherapy (SBRT) may work synergistically, and recent trials have supported this. We hypothesise that adding SBRT to CPI treatment can improve response rates in patients with mCRPC.Methods and analysis The CheckPRO trial is an open-label, randomised, two-stage, phase II trial. We aim to enrol and randomise 80 evaluable patients with mCRPC who progressed following ≥2 lines of treatment. Enrolment started in November 2019 with 38 months expected enrolment period. The participants receive treatment for 52 weeks including four cycles of ipilimumab and nivolumab with or without concomitant SBRT (24 Gray in three fractions) to a single soft tissue or bone metastasis, followed by 10 cycles of nivolumab. Participants are followed until progression, death, or for 12 months after the end of treatment.Co-primary endpoints are the objective response rate and prostate-specific antigen (PSA) response rate. Secondary endpoints include safety, radiographic progression-free survival, clinical benefit rate, duration of response, PSA-progression-free survival beyond 12 weeks, quality of life and overall survival. Exploratory endpoints include translational analyses of tumour biopsies and consecutive blood samples. Biopsies from metastatic sites are collected at baseline, before the third treatment and at the end of treatment. Blood sampling for immune monitoring and circulating tumour DNA is performed consecutively at baseline and every radiographic assessment.Ethics and dissemination This study follows the Helsinki Declaration and is approved by the Danish Ethics Committee System (journal no. H-19016100). All participants must receive written and oral information and provide a signed informed consent document prior to inclusion. The study results will be published in an international peer-review journal.Trial registration number EudraCT number: 2018-003461-34. clinicaltrials.gov ID NCT05655715.